Pembuatan Pembuatan Penyegar Wajah dari Ekstrak Rumput Laut (Eucheuma cottonii) dan Air Bunga Telang (Clitoria ternatea) untuk Masyarakat Pesisir di Tuban - Aliyyah, Hibbah Tukhfatul; Sri Usodoningtyas; Octaverina Kecvara Prithasari; wilujeng, Biyan Yesi Wilujeng (Journal of Beauty and Cosmetology (JBC), 2022)
Face fresheners used by the public today contain more high alcohol, so they are not suitable for dry facial skin types. The use of seaweed extract as a natural ingredient to make traditional facial fresheners for dry facial skin is a solution because of the content of bioactive compounds and carrageenan in seaweed very good for skin. This study aims to determine the most appropriate proportion of face freshener and the content of face freshener preparations in an analytical laboratory based on the results of phytochemical tests. This study used an experimental method with independent variables namely the proportion of seaweed extract and water butterfly pea with a ratio of 2 ml: 98 ml, 4 ml: 96 ml, 6 ml: 94 ml. The dependent variable is the finished face freshener including color, aroma, texture, absorption and preference of the panelists. The results of the phytochemical test on samples of seaweed extract, sea cucumber water and facial freshener samples showed positive results which proved that there were still bioactive compounds in them so that seaweed extracts were suitable as active ingredients for making facial fresheners where sample C had the highest average value in all aspects of the physical test and the panelists' preferences, namely the content of 6 ml of seaweed extract: 94 ml of butterfly pea flower wate Keywords: Butterfly pea flower; facial freshener; seaweed.